Inhibition of NO synthase activity in nervous tissue leads to decreased motor activity in the rat - Halcák, L; Pechánová, O; Zigová, Z; Klemová, L; Novacký, M; Bernátová, I (Physiological research, 2000)
The nitric oxide/cGMP system has been shown to play a crucial role in the mechanism of learning and memory. The aim of the present study was to investigate whether the inhibition of NO synthase in brain regions leads to alterations of spontaneous behavior in rats. Male Wistar rats were treated with NO synthase inhibitor N(G)-nitro-L-arginine methyl ester (L-NAME) at the dose of 40 mg/kg/day. After 4 weeks of L-NAME treatment, NO synthase activity was significantly decreased by 75% in the cerebellum, by 71% in the cerebral cortex and by 72% in the thoracic spinal cord. Decreased NO synthase activity in the nervous tissue was associated with decreased motor horizontal and vertical activities as well as by lowered frequency of sniffing, cleaning and defecation. It is concluded that the inhibition of NO synthase activity has a suppressive effect on spontaneous behavior of rats.
Keywords: Male; NG-Nitroarginine Methyl Ester; Rats, Wistar; mozeček; Motor Activity; Animals; potkani Wistar; NG-nitroargininmethylester; Enzyme Inhibitors; mužské pohlaví; inhibitory enzymů; Cerebellum; pohybová aktivita; krysa rodu Rattus; mícha; Nitric Oxide Synthase; Rats; Spinal Cord; mozek; zvířata; Cerebral Cortex; synthasa oxidu dusnatého; Brain; mozková kůra